DAMPAK KEBIJAKAN FISKAL TERHADAP KINERJA SEKTOR PERTANIAN DI PROVINSI RIAU - Dinda Julia, Alla Asmara; Heriyanto Heriyanto (DINAMIKA PERTANIAN, 2015)
Growth in the agricultural sector in Riau Province slowed from year to year so it needs the appropriate fiscal mechanisms. This research aims to analyze the factors affecting fiscal revenues and expenditures in the agricultural sector in the province of Riau, analyzing the impact of changes in fiscal revenues and expenditures on the performance of the agricultural sector in the province of Riau, and formulate appropriate fiscal policy conducted in the province of Riau. Econometric analysis carried out by the simultaneous equation estimation methods Two Stage Least Squares (2SLS). The results showed that (1) factors affecting fiscal revenues and expenditures is the GDP, revenue, expenditure economic sectors, the total reception area, population, population density, and the rest of the budget of the previous year with a positive impact, as well as the total regional spending and DAU with negative effects, (2) Changes in fiscal policy positive impact on the agricultural sector, especially food crops, (3) fiscal policy is appropriate to increase the performance of the agricultural sector Riau Province is the increase in spending agricultural sector 10% to the GDP agriculture increased 0.67% and agriculture increased labor absorption 0.16%.